Use of starch‐based fat replacers in foods as a strategy to reduce dietary intake of fat and risk of metabolic diseases. Issue 1 (3rd December 2019) - Chen, Yuwei; She, Yongbo; Zhang, Ruisan; Wang, Jieying; Zhang, Xiaohua; Gou, Xingchun
Abstract: Cardiovascular disease (CVD) has emerged as one of the leading causes of death worldwide. Elevated blood cholesterol and low‐density lipoprotein levels are crucial risk factors that contribute to the development of CVD and other metabolic diseases. Dietary fat is believed to be the key factor in modulating circulating cholesterol levels. Thus, reducing dietary intake of fat appears to be an effective strategy to reduce the risk of heart disease. Also, excessive intake of fat and high‐calorie foods is also related to the development of obesity, which contributes to the development of CVD. Therefore, the consumption of low‐fat low‐calorie foods is part of a healthier dietary pattern. However, simply removing fat from foods may lead to compromised overall quality and reduced acceptance of the food products. Thus, fat replacers have emerged as ideal alternatives to dietary fat, which can not only reduce the overall fat and calorie content of the foods but also mimic the physiochemical properties of dietary fat. Starch‐based fat replacers are one kind of fat mimetic that can be produced either chemically as modified starch or enzymatically as maltodextrins. Both modified starch and maltodextrins have been demonstrated to have a promising ability to improve the overall quality of reduced‐fat foods. Modified starch granules act directly as fat globules in modulating the structure and sensory characteristics of the foods, whereas maltodextrins can form thermoreversible gels. Both modified starch granules and maltodextrins can create a fat‐like mouthfeel and therefore are potential fat replacers. This review article aims to discuss the following topics: (a) the effect of carbohydrates and fat on human cardiovascular health and other disease risks, (b) the functionality of starch‐based fat replacers in foods, (c) the applications of starch‐based fat replacers in various foods, and (d) the current and future market value of starch‐based fat replacers. Abstract : This review article discusses the following objectives: (a) effect of carbohydrate and fat on human cardiovascular health and other disease risks, (b) functionality of starch‐based fat replacers in foods, (c) applications of starch‐based fat replacers in various foods, and (d) current and future market value of starch‐based fat replacers.